On the Lebesgue constants of Fourier-Laplace series by Riesz Means - Rasedee, Ahmad Fadly Nurullah; Rakhimov, Abdumalik; Akhmedov, Anvarjon; Hassan, Torla (Institute of Physics Publishing, 2017)
An asymptotic formula for the Lesbegue constant of the Riesz means of Fourier-Laplace series on the sphere obtained in this paper.